Ontological Metaphorsin Pink Floyd’sselected Songs - Muhammad Amin Akbar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study is about the analysis of ontological metaphors in Pink Floyd’s selected songs based on the metaphors theory by Lakoff and Johnson. In Lakoff and Johnson theory, metaphors are divided into structural metaphors, oriental metaphors, and ontological metaphors.The author uses qualitative methods in conducting this research. Researchers focused on written data in the form of scripts from lyrics of Pink Floyd selected songs. The researcher uses Jan Mukarovsky's dynamic structuralism approach. There is a relationship between ontological metaphors, social commentary, and idealism. The purpose of this study is so that people can know the impact of ontological metaphors in songs. If they are aware, then this will benefit themselves and the people around them. This research concludes that Pink Floyd often uses ontological metaphors to convey their metaphorical expression and idealism. From this ontological metaphor in Pink Floyd's selected songs, there are plots, characters, themes, and points of view that can be analyzed.